Evaluation and improvement of integrated pig farming systems in Kerala - Kannan A (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 2005)
The Evaluation of existing pig farming systems of Kerala and the productivity and economic viability of integrated pig-crop/vegetable-fish farming system were studied. A total of 200 pig farmers from five different agroclimatic zones were selected and surveyed using a questionnaire and personal interview. The socio-economic and educational levels of pig farmers and the management practices adapted were analysed. The problems and constraints in pig production were also evaluated. The pig farmers in Kerala belonged to the age group of 31 to 50 years with average monthly income between Rs.4001 to 6000. Christians followed by Hindus but no Muslim took up pig farming. The other agricultural cultivations were coconut, banana, vegetables and arecanut cultivation with the subsidiary animal husbandry activity of cattle rearing and fish farming in costal areas. The rationale behind rearing of pigs was as a source of additional income and majority of the pig farmers had nine to 12 years of experience. Exotic crosses were chiefly preferred to the Desi crosses. Drove was obtained equally from both the government and private farms. A high percentage of pig farmers had herd strength of more than 50 animals with a litter size at birth of nine to 12 and litter size at weaning of seven to nine. Farmers maintained the stock for both fattening and breeding and batch system of fattening was favoured. Swill feeding was the major feeding method and the common feeding frequency was twice daily. The distance between the farm premises and the source of swill ranged from six to10 km and three wheelers were the chief mode of swill transportation. The animals were kept commonly under permanent houses with concrete floor and fully covered thatched roof. The most preferred disposal method was based on live weight. The chief manpower was from family labour. Digestive disorder and ‘Mastitis Metritis Agalactia’ (MMA) were the major problem in adult pigs. The breeding management was the prime concern regarding training need and finance was the main constraint. The farmers were in lack of awareness for vaccination and control of ectoparasites. The farmers have adopted integrated farming in all the agroclimatic zones and showed interest on biogas production, expansion of farm and management through cooperative societies assistance. Twelve progressive farmers of each from Kaiparambu and Kuzhoor Panchayat, Thrissur district of Kerala were supplied with eight Large White Yorkshire grower pigs which were reared under different combination as Pig farming alone as a control group (T1), Pig rearing and Crop/vegetables cultivation (T2) and Broiler chicken, Pig and Fish farming along with crop/vegetables cultivation (T3). The experimental animals in all the three groups were raised on swill and feeding the waste generated by the other components. The other components of integration were a) crop (banana)/ vegetables (Amaranthus, Brinjal, Bindi and Chilli), b) fish (Indian catfish and Assam Vazha) and c) Broiler chicken (Vencob). The parameters like body weight, average monthly and daily weight gains, average daily feed intake, feed conversion efficiency, linear body measurements and carcass traits of pigs on swill feed showed no significant difference and all the combinations of integration were equally effective with respect to all the above parameters. The chicken waste had higher CP content. The average yield and Biomass production of crop/ vegetables, and total yield and average body weight of broiler in different treatments were not statistically significant. However, different varieties of fish within the treatments showed significant difference in their yield and mean body weight. In integrated farming, the net income (Rs) for pigs without integration (10527 .38) was significantly lower than pigs with banana crop (16715.88), pigs with vegetables (12306.38), pigs with banana, fish and chicken (31476.87) and pigs with vegetables, fish and broiler chicken (27129.88). The combination of pig with banana crop had relatively higher return than pig without integration; pig with vegetable; pig with banana crop, fish and broiler chicken and pig with vegetables, fish and broiler chicken and hence the combination of pig and banana is recommended for the marginal farmers of Kerala.